How to Restore Invertebrate Diversity of Degraded Heathlands? A Case Study on the Reproductive Performance of the Field Cricket Gryllus campestris (L.) - Vogels, Joost J.; Verberk, W. C. E. P.; Kuper, J. T.; Weijters, M. J.; Bobbink, R.; Siepel, H. (Frontiers in Ecology and Evolution, 2021)
Background: Nitrogen (NOx, NHy) and acidifying (NOx, NHy, SO¬x) deposition has reduced the biodiversity of European dry heathlands. Restoration efforts such as sod-cutting (removal of vegetation, litter and humus layer) often shifted these systems from N to P limitation and have had limited success in restoring the invertebrate community. Possible reasons for this include the unresolved acidification and a change in food plant stoichiometry. Here, we investigate how liming and P addition change food nutritional quality and their consequences on invertebrate performance. Methods: We performed feeding experiments with field crickets (Gryllus campestris), using plant material collected from a full factorial field experiment with liming and P addition. We related female reproduction as measure of individual fitness to elemental ratios of plants fed to the crickets. Results: P addition stimulated cricket daily reproduction and shortened their reproductive period, resulting in no difference in total reproduction. Liming greatly reduced both daily and total reproduction and resulted in more females cannibalising on their male mates. Females that did so could partly offset the liming induced reduction in reproduction, suggesting dietary deficiency. P-addition improved food quality (lower N:P ratios) while liming led to skewed Mg:Mn and Mg:Fe ratios that compare unfavourably to ratios found in terrestrial invertebrates. Conclusion: Increased plant N:P ratio following sod-cutting constrains the reproductive potential in Gryllus campestris in a non-linear way. Liming reduced nutritional quality, likely by inducing deficiencies in Fe or Mn. Management implications: High-impact restoration management practices such as sod cutting and liming cause new problems for invertebrates rooted in ecological stoichiometry. Since P-addition only partially offsets these negative effects, we instead advocate the use of less intensive N removal management and weaker buffering agents to reduce soil acidification. Furthermore, a reduction in N emission is paramount as it will remove the need for disruptive interventions.